Escalation in high fat intake in a binge eating model differentially engages dopamine neurons of the ventral tegmental area and requires ghrelin signaling. (October 2015) - Valdivia, Spring; Cornejo, María P.; Reynaldo, Mirta; De Francesco, Pablo N.; Perello, Mario
Highlights: Four daily accesses to HFD for 2 h induce hyperphagia with an escalating profile. Four daily accesses to HFD for 2 h induce differential activation of neurons of the mesolimbic pathway. Four daily accesses to HFD for 2 h induce activation of the hypothalamic orexin neurons. Orexin signaling blockage fails to affect escalation of HFD intake. Ghrelin receptor deficient mice fail to escalate the HFD consumption over the successive days of exposure. Abstract: Binge eating is a behavior observed in a variety of human eating disorders. A d libitum fed rodents daily and time-limited exposed to a high-fat diet (HFD) display robust binge eating events that gradually escalate over the initial accesses. Intake escalation is proposed to be part of the transition from a controlled to a compulsive or loss of control behavior. Here, we used a combination of behavioral and neuroanatomical studies in mice daily and time-limited exposed to HFD to determine the neuronal brain targets that are activated – as indicated by the marker of cellular activation c-Fos – under these circumstances. Also, we used pharmacologically or genetically manipulated mice to study the role of orexin or ghrelin signaling, respectively, in the modulation of this behavior. We found that four daily and time-limited accesses to HFD induce: (i) a robust hyperphagia with an escalating profile, (ii) an activation of different sub-populations of the ventral tegmental area dopamine neurons and accumbens neurons that is, in general, more pronounced than the activation observed after a single HFD consumption event, and (iii) an activation of the hypothalamic orexin neurons, although orexin signaling blockage fails to affect escalation of HFD intake. In addition, we found that ghrelin receptor-deficient mice fail to both escalate the HFD consumption over the successive days of exposure and fully induce activation of the mesolimbic pathway in response to HFD consumption. Current data suggest that the escalation in high fat intake during repeated accesses differentially engages dopamine neurons of the ventral tegmental area and requires ghrelin signaling.